Animation for Visualization: Opportunities and Drawbacks - Fisher, Danyel (Beautiful Visualization, 2010)
Does animation help build richer, more vivid, and more understandable visualizations, or simply confuse things?
Complete book avaialble at http://oreilly.com/catalog/0636920000617/